Die Entwicklung des atlantischen Kabeljaubestandes vor Grönland in der zweiten Hälfte des 20. Jahrhunderts - Rätz, Hans-Joachim (1997)
Based on the results of an analytical assessment, the Atlantic cod stock off Greenland collapsed already in the late 60s and, since then, reached rarely the 10 % level of its size in 1955. Applying the concept of a self-sustaining stock, the drastic harvesting strategy of the past four decades must be considered inadequate. The stock collapse was therefore found consistent with annual exploitation rates being not adjusted to conservative management options and exceeding the productivity of the stock by far. The results of a multiplicative model explained the following recruitment failure based on significant effects of spawning stock size as well as temperature. Certainly, cold periods have negatively affected the recruitment process and consequently contributed to the stock collapse. However, such ecological effects should not be itemized causal but must be taken into account regarding appropriate stock management. Till today, the spawning stock remained severely depleted causing a low probability of a successful recruitment and a substantial stock recovery.